The potential application of exfoliated MoS2 to aqueous lithium-ion batteries - Santanu Mukherjee (Electrochemistry Communications, 2022)
Cost-effective storage remains one of the greatest challenges facing the adoption of renewable energy generation. Herein we present a cost-effective aqueous rechargeable battery based on MoS2. Increased discharge capacities are achieved by liquid-phase exfoliation, resulting in a 105% increase in capacity and prolonged lithiation plateau. Contributing evidence is provided by High Resolution TEM investigation of the expanded van der Waals gap between adjacent MoS2 layers and particle active surface area. Exfoliated MoS2 and a MoS2/graphite composite cathode is also investigated, resulting in an increase of reversible lithiation levels over 3x that of the base exfoliated material. The preservation of discharge capacities and voltages indicates the composite is highly effective in improving reversible lithiation. Further examination of the cost-effectiveness of the composite reveals vastly superior storage-to-cost ratios relative to other ARB cathodes.